Rape talks louder than guns feminising men via wartime rape in Judith Thompson's Palace of the End - Salih, Elaff Ganim; Jujar Singh, Hardev Kaur; Bahar, Ida Baizura; Hassan, Mohamad Fleih (Universiti Putra Malaysia Press, 2018)
Wartime rape is a widespread phenomenon that accompanies most wars and conflicts, especially contemporary ones, yet there is much misconception about it. Earlier studies done on war rape focused exclusively on the experiences of female victims. Men as victims of war rape is a topic not many are familiar with or even aware of. The inclusion of men as victims of rape is very rare in society. Moreover, the rape of women often finds its way to the stage, but not the rape of men. Thus, the rape of men in time of war has been overlooked due to unfamiliarity with the topic or to the myth of the invulnerability of man to rape. More importantly, wartime man rape is not taken into consideration as a strategic weapon. Thus, the present study aims to explore the sexual victimisation of men in times of war as an orchestrated combat tool. It investigates the reasons why American combatants raped Iraqi prisoners in Judith Thompson's play Palace of the End. Inger Skjelsbæk’s Social Constructionist Concept is used to explain the rationale behind wartime man rape and to map out the mechanism of its victimisation and perpetration. The present study concludes that men can be victimised like women by rape. In addition, the present study contributes a new understanding of the strategic function of rape with the inclusion of male rape. More importantly, it concludes that the rape of male prisoners in this play is not a natural consequence of war stemming from sensuality or abnormality but a pre-planned institutional act to dominate the perceived enemy.